Modelling antecedents of safety compliance: Incorporating theory from the technological acceptance model - Hu, X.; Griffin, Mark; Bertuleit, M. (Elsevier BV, 2016)
© 2016 Elsevier Ltd. Research into the technology acceptance model (TAM) and safety performance was used to develop a model in which perceived organizational and supervisor support for safety affect employees' compliance with a risk-awareness safety procedure via cognitive-motivational mechanisms. Cross-sectional survey data were collected from 374 employees of a large Australian mining company. Results of path analysis show that both perceived organizational safety support and perceived supervisor safety support influenced compliance with the risk-awareness procedure, although through different cognitive-motivational processes. Perceived organizational safety support was significantly associated with compliance via perceived usefulness of the risk-awareness procedure. On the other hand, perceived supervisor safety support was significantly related to compliance via safety motivation. The implications for theory and practice are discussed.